P5_10 Could Titans Actually be Fought? - Ruprai, Amrik; Agrawal, Rusi; Shaikh, Hasan; Singh, Jagraj (Physics Special Topics, 2021)
This paper investigates the use of omnidirectional manoeuvre gear in the animated series Attack onTitanandthepossibilityforhumanbeingstousethegearandremainunharmedwhencon- sidering the physical affects on the body.In the scene examined the user experienced a G force of 7.18m3/kg/s2, an impact force of 119,000 N and utilised a reaction time of 0.0139 s.